Antiliberalism as key to Koselleck’s work - Galindo Hervás, Alfonso (2018)
In this article I defend that the criticism about the liberalism can be considered a key in order to unify the Koselleck’s theoretical projet. His point of view anti-liberal has its origins in the influence of Schmitt’s thought, and it is stated explicitly in the thesis from Crítica y crisis and the revitalization of motto Historia magistra vitae.